PERSEPSI MAHASISWA PPLK TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG TERHADAP BIMBINGAN GURU PAMONG - 1623-1639 , Andriani Utami (CIVED, 2016)
ABSTRACTThis study is purposed to find out student’s perception toward counselor in report counseling where study population is students of Construction Engineering Study Program who have finished PPLK program on semester of July to December 2015. This studi was descriptive research with quantitative approach. Sampling was performed by Total Sampling. Study finding shows that counselor roles in report counseling based on student’s perception are: (1) Counselor guidance is categorized as good during PPLK activities that is 40.74%, (2) During orientation/ field introduction activities, counselor guidance is categorized as good that is 48.15%, (3) Counselor guidance during teaching training activities is categorized as good that is 46,30%, to which consists of guided teaching practice (LMT) in good category of 38.89% and autonomous teaching practice (LMM) in moderate category of 29,63%, (4) Counselor guidance is categorized as moderate during learning test that is 24.07%, (5) Counselor guidance is categorized as moderate non-teaching activities that is 33.33%. Keywords: Perception, PPLK Student, Counselor